2016
DOI: 10.1111/medu.13062
|View full text |Cite
|
Sign up to set email alerts
|

‘Sometimes the work just needs to be done’: socio-cultural influences on direct observation in medical training

Abstract: The cultural values of autonomy in learning and practice and efficiency in health care provision challenge the integration of direct observation into clinical training. Medical learners are often expected to ask for observation, but such requests are socially and culturally fraught, and likely to constrain the wider uptake of direct observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
141
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(145 citation statements)
references
References 41 publications
4
141
0
Order By: Relevance
“…Direct observation is fundamental to both trustworthy assessment and credible feedback. Learners, however, maintain some ambivalence about direct observation during their clinical education: they recognise that it has value, but also identify a certain discomfort with being observed that shapes how they respond . For learners, being observed typically feels like being assessed .…”
Section: Learner Perceptionsmentioning
confidence: 99%
“…Direct observation is fundamental to both trustworthy assessment and credible feedback. Learners, however, maintain some ambivalence about direct observation during their clinical education: they recognise that it has value, but also identify a certain discomfort with being observed that shapes how they respond . For learners, being observed typically feels like being assessed .…”
Section: Learner Perceptionsmentioning
confidence: 99%
“…There is a wealth of research findings showing that exactly the culture (i. e. ‘the way we do things around here’) and contextual factors as described above may interfere with assessment quality. In medicine, for example, research findings clearly show that cultural values of autonomy in learning and practice, as well as aims to maximize efficiency in delivery of health care services, conflict with a culture that values direct observation or documentation of meaningful performance data [6, 12, 13]. In fact, cultural context may be the key factor determining trustworthiness of entrustment decisions.…”
mentioning
confidence: 99%
“…Clearly, health care and health care systems represent complex contexts, in which different organisational identities, goals, norms and values may drive tensions between learning and performance. Obviously, the tensions of competing goals in the delivery of high‐quality, efficient patient care, as well as high‐quality, efficient teaching and learning, are likely to become more salient under conditions of limited resources and increasing pressures for accountability . In health care settings, learning–performance tensions may surface if an individual is required to fulfil the multiple roles of learner as well as health care provider (trainees), or health care provider, coach and assessor (clinicians).…”
Section: Polarities and Tensions In Assessment: Categorisation And Dementioning
confidence: 99%